Epidemiology of Culture-confirmed Candidemia Among Hospitalized Children in South Africa, 2012–2017. Issue 8 (16th April 2021) - Shuping, Liliwe; Mpembe, Ruth; Mhlanga, Mabatho; Naicker, Serisha D.; Maphanga, Tsidiso G.; Tsotetsi, Ernest; Wadula, Jeannette; Velaphi, Sithembiso; Nakwa, Firdose; Chibabhai, Vindana; Mahabeer, Prasha; Moncho, Masego; et al.
Abstract : Background: We aimed to describe the epidemiology of candidemia among children in South Africa. Methods: We conducted laboratory-based surveillance among neonates (≤28 days), infants (29 days to <1 year), children (1–11 years) and adolescents (12–17 years) with Candida species cultured from blood during 2012–2017. Identification and antifungal susceptibility of viable isolates were performed at a reference laboratory. We used multivariable logistic regression to determine the association between Candida parapsilosis candidemia and 30-day mortality among neonates. Results: Of 2996 cases, neonates accounted for 49% (n = 1478), infants for 27% (n = 806), children for 20% (n = 589) and adolescents for 4% (n = 123). The incidence risk at tertiary public sector hospitals was 5.3 cases per 1000 pediatric admissions (range 0.39–119.1). Among 2943 cases with single-species infections, C. parapsilosis (42%) and Candida albicans (36%) were most common. Candida auris was among the 5 common species with an overall prevalence of 3% (n = 47). Fluconazole resistance was more common among C. parapsilosis (55% [724/1324]) versus other species (19% [334/1737]) ( P < 0.001). Of those with known treatment (n = 1666), 35% received amphotericin B deoxycholate alone, 32% fluconazole alone and 30% amphotericin B deoxycholate with fluconazole. The overall 30-day in-hospital mortality was 38% (n = 586) and was highest among neonates (43% [323/752]) and adolescents (43% [28/65]). Compared with infection with other species, C. parapsilosis infection was associated with a reduced mortality among neonates (adjusted odds ratio 0.41, 95% confidence interval: 0.22–0.75, P = 0.004). Conclusions: Candidemia in this setting mainly affected neonates and infants and was characterized by fluconazole-resistant C. parapsilosis with no increased risk of death.